2004
DOI: 10.1021/ja040054z
|View full text |Cite
|
Sign up to set email alerts
|

Selective Coupling of Methylene Groups at a Rh/Os Core, Yielding C2, C3, or C4Fragments:  Roles of the Adjacent Metals in Carbon−Carbon Bond Formation

Abstract: The mixed-metal complex, [RhOs(CO)(4)(dppm)(2)][BF(4)] (1; dppm = micro-Ph(2)PCH(2)PPh(2)) reacts with diazomethane to yield a number of products resulting from methylene incorporation into the bimetallic core. At -80 degrees C the reaction between 1 and CH(2)N(2) yields the methylene-bridged [RhOs(CO)(3)(micro-CH(2))(micro-CO)(dppm)(2)][BF(4)] (2), which reacts further at ambient temperature to give the allyl methyl species, [RhOs(eta(1)-C(3)H(5))(CH(3))(CO)(3)(dppm)(2)][BF(4)] (4). At intermediate temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 39 publications
5
77
0
Order By: Relevance
“…Broad-band 31 P decoupling also sharpens the 1 H signal for the μ-13 CH 2 protons, allowing a weak 1.6 Hz coupling to Rh to be observed; two-bond Rh-H coupling of less than 3 Hz is typical. 8 Even with broad-band 31 P decoupling, the dppm-H methanide resonance shows no resolved coupling to Rh.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad-band 31 P decoupling also sharpens the 1 H signal for the μ-13 CH 2 protons, allowing a weak 1.6 Hz coupling to Rh to be observed; two-bond Rh-H coupling of less than 3 Hz is typical. 8 Even with broad-band 31 P decoupling, the dppm-H methanide resonance shows no resolved coupling to Rh.…”
Section: Methodsmentioning
confidence: 99%
“…This transformation occurred within 3 h in refluxing THF and within 30 min in refluxing benzene; however, at these temperatures, subsequent transformation to 7b also began to occur (see procedure g). A yellow solid was isolated from the ambient-temperature reaction upon removal of the solvent in vacuo, and this solid was rinsed with 2 Â 0.5 mL of pentane and dried further in vacuo (48 mg, 96% (8). To a solution containing a mixture of 6a and 6b (100 mg, 0.084 mmol) in 5 mL of THF was added 11 μL of DMAD (0.090 mmol, 1.05 equiv), resulting in a color change from orange to dark red.…”
Section: ' Introductionmentioning
confidence: 99%
“…Similar couplings have also been observed with other htb systems. 7 Despite the high stability of NHC ligands and the significant electronic and steric differences that exist between methylene and NHC groups, we believed that if htb complexes with NHC ligands anchored onto the bimetallic framework were available, coupling reactions between NHC groups and other ligands, hitherto quite rare, might be promoted by the htb centers. 8 We have reported that the reaction of [W(CO) All four CO groups in the cluster are interacting with more than one metal.…”
mentioning
confidence: 99%
“…They focused on the relevance of the bridging methylene groups and the role of the two different metals (Rh and Os). 88 Mixing [RhOs(CO) 4 (dppm) 2 ](BF 4 ) compound 5 with diazomethane led to formation of complex 8, which is likely formed by a series of consecutive carbene insertions (Scheme 25). 89 In order to get a better insight into the mechanism of this methylene-coupling reaction, the reaction was performed at different temperatures.…”
Section: Fischer-tropsch Synthesismentioning
confidence: 99%
“…This, however did not provide much more information regarding the formation of 7 and 8. 88 Further information was obtained by adding diazomethane to vinylidene-bridged species (Scheme 26). This leads to similar types of carbene insertion reactions with a comparable temperature dependency, 91 and shows that carbene insertion into bridging positions is possible.…”
Section: Fischer-tropsch Synthesismentioning
confidence: 99%